2013
DOI: 10.1002/asia.201300418
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Phenylmethanethiolate‐Protected Au20(SR)16 and Au24(SR)20 Nanoclusters and Insight into the Kinetic Control

Abstract: We report two synthetic routes for concurrent formation of phenylmethanethiolate (-SCH2Ph)-protected Au20(SR)16 and Au24(SR)24 nanoclusters in one-pot by kinetic control. Unlike the previously reported methods for thiolate-protected gold nanoclusters, which typically involve rapid reduction of the gold precursor by excess NaBH4 and subsequent size focusing into atomically monodisperse clusters of a specific size, the present work reveals some insight into the kinetic control in gold-thiolate cluster synthesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…This 20-gold-atom cluster was not in the series of Au n (SG) m clusters reported in the classic work by Negishi et al 16 Zhu et al first observed this size in a size-controlled synthesis of phenylethylthiolate-protected gold nanoclusters in 2009. 42 The Au 20 (SC 2 H 4 Ph) 16 synthesis was done by a kinetically controlled method; specifically, the Au(III) reduction to Au(I) by excess thiol and the subsequent aggregation of Au(I) to the [Au (I) 43 The Au 20 (SR) 16 cluster is charge neutral. The optical absorption spectrum of Au 20 (SC 2 H 4 Ph) 16 shows a distinct band at ∼ 485 nm and a weak band at ∼420 nm, as shown in Fig.…”
Section: Au 20 (Sr) 16mentioning
confidence: 99%
“…This 20-gold-atom cluster was not in the series of Au n (SG) m clusters reported in the classic work by Negishi et al 16 Zhu et al first observed this size in a size-controlled synthesis of phenylethylthiolate-protected gold nanoclusters in 2009. 42 The Au 20 (SC 2 H 4 Ph) 16 synthesis was done by a kinetically controlled method; specifically, the Au(III) reduction to Au(I) by excess thiol and the subsequent aggregation of Au(I) to the [Au (I) 43 The Au 20 (SR) 16 cluster is charge neutral. The optical absorption spectrum of Au 20 (SC 2 H 4 Ph) 16 shows a distinct band at ∼ 485 nm and a weak band at ∼420 nm, as shown in Fig.…”
Section: Au 20 (Sr) 16mentioning
confidence: 99%
“…39 Similar quasi/irreversible electrochemical behaviour has been reported for Au 20 (SC 2 H 4 Ph) 16 and Au 24 (SC 2 H 4 Ph) 20 clusters, with generally a broad peak at $À1.0 V vs. Ag/AgCl. 59 One can conclude that the electronic (and even crystal) structures of Au 20 , Au 23 and Au 24 are similar in terms of the origin of the HOMO and LUMO orbital locations and properties. Further optical properties were investigated using photoluminescence (PL) spectrometry.…”
mentioning
confidence: 89%
“…[ 104 ] This method can be further modified to achieve Au NC synthesis in one phase, using a polar solvent like tetrahydrofuran (THF) and methanol. [ 4 ] A wide range of hydrophobic thiolate ligands can be used in this method, and some successful examples are Au 24 (SCH 2 Ph) 20 , [ 54 ] Au 44 (TBBT) 28 (TBBT = 4‐tert‐butylbenzenethiolate), [ 77 ] Au 64 (S‐ c ‐C 6 H 11 ) 32 (S‐ c ‐C 6 H 11 = cyclohexanethiolate), [ 105 ] and Au 25 (SC 2 H 4 Ph) 18. [ 106 ] The reaction conditions, such as temperature and stirring rate, can also be used to further control the reaction kinetics to synthesize different sized Au NCs.…”
Section: Ligands’ Effects On the Synthesis Of Ligand‐protected Au Ncsmentioning
confidence: 99%